Comprehensive Quantitative Spatiotemporal Gait Analysis Identifies Gait Characteristics for Early Dementia Subtyping in Community Dwelling Older Adults - De Cock, Anne-Marie; Fransen, Erik; Perkisas, Stany; Verhoeven, Veronique; Beauchet, Olivier; Vandewoude, Maurits; Remmen, Roy (Frontiers in Neurology, 2019)
Background: Gait patterns were associated with cognitive impairment stages. The current study examined the relation between dementia type and spatiotemporal gait characteristics under different walking conditions in pre and mild neurocognitive disorder stages. Methods: Community-dwelling older adults (age 50+) with memory complaints underwent, at baseline and during follow-up (every four months), a standard dementia assessment and a comprehensive spatiotemporal gait analysis (walking on an electronic walkway at usual pace (UP) with and without a counting-backwards (CW) or animal-reciting dual-task (AW), at fast (FP) and at slow (SP) pace). At baseline the participants were categorised according to the Clinical Dementia Rating (CDR) scale. At the end of the study, the dementia diagnosis was used to stratify the categories in three outcome groups: developed ‘No-dementia’, ‘AD+FTD’ (grouping Alzheimer’s or Fronto-temporal dementia) or ‘VascD+LBD’ dementia (grouping Vascular dementia or Lewy body dementia). The gait characteristics were compared per category in paired groups. Sub-analysing in the ≥70-years-old participants evaluated the age effect. Results: Five hundred and thirty-six participants, age 50-to-95-years old were followed for 31-to-41 months. In the CDR 0, no differences were seen between eventual dementia and no-dementia individuals. In the CDR 0.5, CW dual task cost (DTC) step width was larger in the imminent ‘AD+FTD’ and AW (normalised) gait speed was slower in the future ‘VascD+LBD’ group compared to the no-dementia participants. Slower UP (normalised) gait speed differed the future ‘VascD+LBD’ from the ‘AD+FTD’ individuals. In the CDR 1: Wider steps in UP, SP and CW differed the ‘VascD+LBD’ from the ‘AD+FTD’ group. In the ≥70-years old CDR 0 category, higher AW cycle time variability in the imminent ‘AD+FTD’ dementia group, wider UP step width and higher AW cycle time variability in the ‘VascD+LBD’ group differed them from the no-dementia group up to three years before dementia diagnosis. The distinctive gait characteristics between the no-dementia and the imminent dementia groups in CDR 0.5 and CDR 1 remained the same as in the overall group. Conclusion: Distinctive spatiotemporal gait characteristics were associated with specific dementia types up to three years before diagnosis. The association is influenced by the cognitive stage and age.